Autophagic tumor stroma: Mechanisms and roles in tumor growth and progression. Issue 1 (26th June 2012) - Zhao, Xianda; He, Yuyu; Chen, Honglei
Abstract Macroautophagy (hereafter autophagy) is a cellular homeostatic mechanism that involves protein and organelle degradation, and has a number of connections to human physiology and diseases. Autophagy in tumor parenchyma acts as either a tumor‐promoting role or a tumor‐inhibiting role depending on the types and stages of tumors. In recent years, attention to autophagy in tumor stroma that is referred as "autophagic tumor stroma" has created a new paradigm to understand the role of autophagy in cancer. Here we propose that the autophagic tumor stroma is a phenomenon of adaptation at a certain stage of tumor development, and has a prominent role in tumor growth, progression and spread of tumors. This idea is supported by recent studies: (i) Autophagic tumor stroma is activated by hypoxia and cancer cells induced oxidative stress, when tumors grow to a certain stage; (ii) Autophagic tumor stroma aids in providing essential nutrients to malignant cells, remodeling the tumor microenvironment, increasing DNA damage, genetic instability and stemness in cancer cells, and decreasing the apoptotic sensitivity of cancer cells. The autophagic tumor stroma is therefore a significant determinant in tumor growth and progression and implicates an important target for cancer therapies.